Pelaksanaan Tradisi Aci Keburan di Pura Hyang Api Desa Pakraman Kelusa, Kecamatan Payangan Kabupaten Gianyar - Kiriana, I Nyoman; Sri Widiasih, Ni Nyoman; Rai Suadnyani, I Gusti Made (Jurnal Penelitian Agama Hindu, 2023)
The development of science and technology has influenced people's mindsets to think scientifically and practically in all aspects of life, including in aspects of religious life as well as in understanding religious teachings, both tattwa, susila, and upakara. Hyang Api Temple is one of the types of Dang Kahyangan, which is located in Pakraman Kelusa Village. Its uniqueness in particular lies in the piodalan ceremony taking place with the implementation of the cockfighting tradition or Aci Keburan in the jaba outer courtyard of the Hyang Api Temple. The purpose of this study was to analyze 1) to know the history of Pekraman Kelusa village, 2) to analyze the form of the Aci Keburan, 3) to analyze the infrastructure of the Aci Keburan, and 4) to analyze the process of implementing the Aci Keburan. The method used in this research is qualitative with an emphasis on observation case studies in the implementation of the Aci Keburan tradition at the Hyang Api Temple, Pekraman Kelusa Village. The results and discussion are the history of Kelusa village starting from the sacred journey of dharmayatra and tirtayatra Maharsi Markandya in Pakraman Kelusa village planting banyan trees. The form of the implementation of the Aci Keburan is piodalan at the Hyang Api which falls every 210 days, namely on Kliwon, Wara Uye is known as Tumpek The cage commemorates the birthday of all livestock. Aci Keburan (naur sesangi) comes from the word "cebur, keber" (from flying continuously down). Tradition Aci at of the rooster which is the main element of Naur Sesangi Pura Hyang fire. The roosters that are being played are killing each chasing other or other, so from this fact it is suspected that this is the background or the term Aci burial, which is a typical offering of the Hyang Api in the village of Pakraman Kelusa.